Daylight Analysis and Lighting Energy Management for Schools in Hot-Temperate Climates - Kutlu, Rana; Yener, Alpin; Manav, Banu; Küçükdoğu, Mehmet (Avery Index, 2012)
The aim of the study is to suggest an optimum facade design and an energy efficient lighting system for elementary schools’ classroom modules for different climate types. A classroom module from the typical projects which are implemented by the Ministry of Public Works and Settlement of Turkey was analyzed, by the aid of the computer based daylight analysis program Radiance 2.0 Beta, and daylight performance was evaluated for hot and temperate climate types. The results are evaluated in terms of monthly and annual energy consumption and a proposal is made to increase visual performance and to reduce energy conservation. The proposal covers envelope design, solar control and artificial lighting system. The principles of facade design, shading device and artificial lighting system are discussed from the view point of energy conscious design for hot and temperate climate types. The study findings suggest an optimum orientation-dependant facade design for the two climate types.
Keywords: Daylighting; Lighting Energy Management; Elementary Schools Classroom Module; Facade Design; Climate Type